2022 IEEE 19th International Symposium on Biomedical Imaging (ISBI) 2022
DOI: 10.1109/isbi52829.2022.9761545
|View full text |Cite
|
Sign up to set email alerts
|

CLIMAT: Clinically-Inspired Multi-Agent Transformers for Knee Osteoarthritis Trajectory Forecasting

Abstract: In medical applications, deep learning methods are built to automate diagnostic tasks. However, a clinically relevant question that practitioners usually face, is how to predict the future trajectory of a disease (prognosis). Current methods for such a problem often require domain knowledge, and are complicated to apply. In this paper, we formulate the prognosis prediction problem as a one-to-many forecasting problem from multimodal data. Inspired by a clinical decisionmaking process with two agents -a radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…However, the MRI pipeline outperformed the X-ray pipeline for subjects without OA and with severe OA. Nguyen et al (2021) predicted OA structural prognosis assessed by KL grade from X-ray and clinical variables and reported BACCs from 0.27 to 0.55 37 . In general, the performance of the models was lower in this study than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MRI pipeline outperformed the X-ray pipeline for subjects without OA and with severe OA. Nguyen et al (2021) predicted OA structural prognosis assessed by KL grade from X-ray and clinical variables and reported BACCs from 0.27 to 0.55 37 . In general, the performance of the models was lower in this study than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that multiple transformers are needed to for such multiple modalities [32]. Therefore, similar to our previous version [22], this study adapts the idea of using multiple transformers in our framework to perform DTF from multiple modalities.…”
Section: Related Workmentioning
confidence: 94%
“…In this paper, we present an extended version of our earlier work on automatic DTF [22], where we proposed a Clinically-Inspired Multi-Agent Transformers (CLIMAT) framework, aiming to mimic the interaction process between a general practitioner / treating physician 1 and a radiologist. In our system, a radiologist module, consisting of a feature extractor (convolutional neural network; CNN) and a transformer, analyses the input imaging data and then provides an output state of the transformer representing a radiology report to the general practitioner -corresponding module (purely transformerbased).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformer is one of the deep learning models with the potential to outperform existing cutting-edge time series models [16]. Transformers have been applied to datasets with long historical information to solve various problems [17], [18], [19], [20], [21], and [22]. According to a recent study, Transformer produces the best results for the time series regression problem compared to other models [23].…”
Section: Introductionmentioning
confidence: 99%